Uno scenario di riconversione ecologica dell’economia - Viale, Guido (Scienze del Territorio, 2018)
The global challenge posed by the start of Anthropocene and climate change is ecological conversion, which is different from green economy, since it is not guided only by market opportunities, but by a conscious and participated plan affecting all aspects of social coexistence. Ecological conversion involves a transition from large centralised plants managed by hierarchical structures to a multiplicity of small plants distributed and managed through participatory processes that must affect both the institutional dimension of local governments and the governance of enterprises. All this entails a radical, albeit gradual and never complete, process of reterritorialisation of productions, markets and monetary circulation, albeit within a global dimension guaranteed by the world web. Local and global coexist by focusing on the former the management of physical processes (atoms), on the latter the information circulation (bits). Key actors of this transformation, which includes a dimension of conflict against the current arrangements of the world-economy and the powers that rule it, can only be municipal administrations, in federalist view that focus economic and political relationships on national, continental and planetary networks of municipalities.